E-Government Interoperability and Integration Architecture Modeling Using TOGAF Framework Based On Service Oriented Architecture - Setiawan, Awan; Yulianto, Erwin (The Asian Journal of Technology Management (AJTM), 2018)
Abstract. Development of e-Government in Indonesia continues to roll and run in every government agency, both in central government and local government. Implementation of e-Government means that there are government's efforts to build and improve the quality of public services and internal operations in each regional apparatus organization effectively and efficiently. These activities inline with one of the bureaucracy reform mission, that is the modernization of government bureaucracy through the using of information and communication technology optimization to support bureaucracy reform vision and the creation of good governance. The development and implementation of e-Government currently mostly implemented by each regional apparatus organization. This condition makes it difficult to exchange data and information related to multisectoral activities due to data and information spread across various databases from different applications, platform, environment and architecture without good documentation. In preparation for arranging the e-Government architecture, we will use The Open Group Architecture Framework - Architecture Development Method as an enterprise architecture framework. The purpose of this research is to study and conceptualize e-Government interoperability and integration solutions of all existing applications and providing some model documents such as e-Government Architecture Vision, Integrated Business Model References Architecture, and Integrated Data Model References Architecture.Keywords: E-Government, interoperability and integration, service oriented architecture, TOGAF-ADM, information and communication technology